Temporal Changes in Reverse Torque of Locking-Head Screws Used in the Locking Plate in Segmental Tibial Defect in Goat Model - Grzeskowiak, Remigiusz M.; Rifkin, Rebecca E.; Croy, Elizabeth G.; Steiner, Richard C.; Seddighi, Reza; Mulon, Pierre-Yves; Adair, Henry S.; Anderson, David E. (Frontiers in Surgery, 2021)
The objective of this study was to evaluate changes in peak reverse torque (PRT) of the locking head screws that occur over time. A locking plate construct, consisting of an 8-hole locking plate and 8 locking screws, was used to stabilize a tibia segmental bone defect in a goat model. PRT was measured after periods of 3, 6, 9, and 12 months of ambulation. PRT for each screw was determined during plate removal. Statistical analysis revealed that after 6 months of loading, locking screws placed in position no. 4 had significantly less PRT as compared with screws placed in position no. 5 (p < 0.05). There were no statistically significant differences in PRT between groups as a factor of time (p > 0.05). Intracortical fractures occurred during the placement of 151 out of 664 screws (22.7%) and were significantly more common in the screw positions closest to the osteotomy (positions 4 and 5, p < 0.05). Periosteal and endosteal bone reactions and locking screw backout occurred significantly more often in the proximal bone segments (p < 0.05). Screw backout significantly, negatively influenced the PRT of the screws placed in positions no. 3, 4, and 5 (p < 0.05). The locking plate-screw constructs provided stable fixation of 2.5-cm segmental tibia defects in a goat animal model for up to 12 months.